International Journal of Anthropology and Ethnology
International Journal of Anthropology and Ethnology is an open access, peer-reviewed, scholarly journal. It considers articles in the fields of Anthropology and Ethnology, concerning theory, policy and practice, especially the critical global issues and challenges people are facing up to all over the world.  It welcomes original research papers, conference summaries, academic interviews, academic debates, research synthesis, fieldwork reports and book reviews. It aims to introduce achievements representing the highest level of anthropological and ethnological studies around the world (not only in China or Asia); promote academic exchanges between western and non-western circles; facilitate dialogues and interactions about the global or regional hot topics; build a platform for communications within the international research communities of anthropology and ethnology.